Analysing the changing relationship between the Brazilian stock market and global economic indicators - Davey, Paul Philip (2007)
This study investigates the relationship between the Brazilian stock market and four independent variables, specifically the US stock market, the Mexican stock market, the exchange rate of the US dollar in terms of Brazilian Real and oil prices. Graphical illustrations of the movement between the Ibovespa and each independent variable were used to identify ten sub periods where the relationship was believed to have changed in some way.